The secret entrance of the "Galerie Breuil" in the Mas d'Azil cave (Ariège, France). (December 2021) - Jarry, Marc; Pallier, Céline; Bruxelles, Laurent; Bon, François; Anderson, Lars; Arrighi, Vincent; Camus, Hubert; Comelongue, Marc; Fritz, Carole; Ghaleb, Bassam; Lejay, Mathieu; Martin, Hélène; et al.
Highlights: The Mas d'Azil cave is a major European site for the Upper Palaeolithic remains that it has yielded but also for the rock art preserved in some galleries. The Breuil gallery is the richest of them, but its access is only possible after the passage of a sedimentary plug accumulated before the Magdalenian occupations. The dating of a calcite flow closing an upper passage leading to the Breuil gallery shows that this passage may have been used by Magdalenian artists. It is therefore necessary to replace the reading of the parietal works in their initial order rather than in that of discovery, since it is most certainly through this that they have accessed the decorated gallery. Abstract: The Mas d'Azil cave is a major site for the study of European prehistory, and the evolution of the discipline itself, especially regarding our understanding of the late Upper Paleolithic. In particular, its mobiliary art is one of the richest and the most beautiful known in a Magdalenian context. Lesser known however, is its rock art. Few publications are devoted to these works of prehistoric art, and despite several field work campaigns we still lack a general synthesized study of them at the scale of the entire cave system. A survey of the Mas d'Azil cave system is currently underway, and the aim of this project is to map the archaeological and geoarchaeological organization of the site. Obtaining a reliable topography of the cave, an endeavor begun in the 1980s but never finished, is essential to resituating the archaeological deposits relative to the various natural processes and formations having affected and conditioned their deposition and conservation, as well as the different historical phases of exploitation of the cave. Using this survey approach, we already have a clearer picture of the repartition of Magdalenian areas and circulation spaces of the right bank. Thus, if the residential areas are located on the upper parts of the cave ( La Rotonde, Galerie Des Silex ), that benefit from more stable and mild temperatures, the lower parts ( Salle Piette, Galerie Rouzaud ) do not appear to have been residential areas. Our approach also shows that the current entrance of the "Galerie Breuil", which is located at the end of one of the lower rooms and is the main decorated part of the cave, was likely unknown to the Magdalenians. They could only have entered the Galerie Breuil via a smaller hidden corridor that was blocked after the Magdalenian occupation, as the growth of the speleothem obstructing this passage dates to 13 000 y BP. The clear difficulty encountered by Magdalenian occupants as they attempted to access this gallery may have contributed to a symbolic separation between residential and symbolic, and therefore decorated, spaces, where access to the latter may have been actively limited and/or controlled. In this paper, we propose to describe the palaeotopography of the cave during the Magdalenian period, supported by the analysis of the stratigraphy, new dates, as well as the historical archives from early excavations. By crossing these different lines of evidence we will investigate the question of accessibility and visibility of prehistoric rock art in a cave that have sometimes been considered a Magdalenian "aggregation site".